La Normalización en México - Béjar Rivera, Luis José (Revista de Derecho, 2019)
Lately in Mexico, an interesting way and fairly useful for allowing an increase in the citizen’s participation in the public administration has been the “normalización” (technical rule making), which drifts between soft law and the general administrative decisions, proposing an important dialogue between the Public Administration and the citizen, mainly to protect consumer’s rights, but also, as an instrument for the purpose of standardizing procedures and public acquisitions. The objective of this work precisely is to analyze the legal nature of these technical dispositions, centered in the Official Mexican Norm (NOM), its administrative procedure of creation and the regulatory agencies.